Synchronous digitization for high dynamic range lock-in amplification in beam-scanning microscopy - Muir, Ryan D. (Author(s)., 2014)
Digital lock-in amplification (LIA) with synchronous digitization (SD) is shown to provide significant signal to noise (S/N) and linear dynamic range advantages in beam-scanning microscopy measurements using pulsed laser sources. Direct comparisons between SD-LIA and conventional LIA in homodyne second harmonic generation measurements resulted in S/N enhancements consistent with theoretical models. SD-LIA provided notably larger S/N enhancements in the limit of low light intensities, through the smooth transition between photon counting and signal averaging developed in previous work. Rapid beam scanning instrumentation with up to video rate acquisition speeds minimized photo-induced sample damage. The corresponding increased allowance for higher laser power without sample damage is advantageous for increasing the observed signal content.